2013
DOI: 10.5194/bgd-10-1605-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiyear precipitation reduction strongly decrease carbon uptake over North China

Abstract: Drought has been a concern of global and regional water, carbon and energy cycles. From 1999 to 2011, North China experienced a multiyear precipitation reduction, which decreased significantly water availability as indicated by decreased soil moisture and Palmer Drought Severity Index. In this study, three light use efficiency models (CASA, MODIS-GPP and EC-LUE) and one dynamic vegetation model (IBIS) were used to characterize the impacts of long-term drought on terrestrial carbon fluxes over the North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Where GPP is the gross primary productivity (g C/m 2 ), FPAR refers to the ratio of plant canopy absorbing photosynthetically active radiation, and the product of FPAR and PAR is the fraction of PAR absorbed by plant canopy. Moreover, an Angstrom-type correlation method was used to calculate downward solar radiation (Rg) from the daylight hours data (Almorox and Hontoria, 2004;Yuan et al, 2013), and Rg was converted to photosynthetically active radiation (PAR) using a ratio of 0.5; ε max is the utilization rate of potential light energy (2.14 g C/MJ), f(T) is the temperature limiting factor, and f(W) is the water limiting factor. FPAR is calculated as: FPAR=a×NDVI+b.…”
Section: Analysis Of Primary Productivitymentioning
confidence: 99%
“…Where GPP is the gross primary productivity (g C/m 2 ), FPAR refers to the ratio of plant canopy absorbing photosynthetically active radiation, and the product of FPAR and PAR is the fraction of PAR absorbed by plant canopy. Moreover, an Angstrom-type correlation method was used to calculate downward solar radiation (Rg) from the daylight hours data (Almorox and Hontoria, 2004;Yuan et al, 2013), and Rg was converted to photosynthetically active radiation (PAR) using a ratio of 0.5; ε max is the utilization rate of potential light energy (2.14 g C/MJ), f(T) is the temperature limiting factor, and f(W) is the water limiting factor. FPAR is calculated as: FPAR=a×NDVI+b.…”
Section: Analysis Of Primary Productivitymentioning
confidence: 99%
“…Utilizing the Moderate Resolution Imaging Spectroradiometer (MODIS) GPP and NPP products, Zhang et al (2012a) reported that the 2010 spring drought caused detectable reductions of GPP and NPP in southwestern China. Using the light use efficiency models CASA, MODIS-GPP, and Eddy Covariance Light Use Efficiency (EC-LUE), along with the dynamic Integrated Biosphere Simulator (IBIS) vegetation model, Yuan et al (2013) found that the carbon sink over North China declined by 0.011 Pg C yr −1 during the 1999-2011 drought period. However, these studies mainly focused on the influence of droughts on GPP and NPP.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the Moderate Resolution Imaging Spectroradiometer (MODIS) GPP and NPP products, Zhang et al (2012a) reported that the 2010 spring drought caused detectable reductions of GPP and NPP in southwestern China. Using the light use efficiency models CASA, MODIS-GPP, and Eddy Covariance Light Use Efficiency (EC-LUE), along with the dynamic Integrated Biosphere Simulator (IBIS) vegetation model, Yuan et al (2013) found that the carbon sink over North China declined by 0.011 Pg C yr −1 during the 1999-2011 drought period. However, these studies mainly focused on the influence of droughts on GPP and NPP.…”
Section: Y Liu Et Al: Impacts Of Droughts On Carbon Sequestrationmentioning
confidence: 99%